Effects of nanomaterials on high performance concrete mortars exposed to elevated temperatures - Farzadnia, Nima (2014)
High performance concrete (HPC) is currently used in massive amounts in the construction industry due to its technical and economical advantages over nor-mal concrete. The HPC is characterized by improved mechanical and durability properties resulting from the use of chemical and mineral admixtures as well as specialized production processes. However, sharp strength loss and reduction in elastic modulus at temperatures below 400 C are major disadvantages of HPC compared to normal concrete; raising questions on its application in the construction industry at high temperatures. The demerit of HPC at elevated temperatures up to 400 C is mostly attributed to a mechanism called hydrothermal process by which cracks and in some cases spalling occur due to vapor pressure. It is caused by the release of water from capillaries as well as degradation of hydration products entrapped in the impermeable microstructure of the HPC, increasing the internal vapor pressure. All this is brought about by the low water to binder ratio in the HPC with the presence of mineral admixtures such as silica fume. Nonetheless, some studies have mentioned the positive effect of mineral admixtures at elevated temperatures due to the formation of stronger clusters of calcium silicate hydrate and restriction in crystal growth of calcium hydroxide. This study investigated the behavior of high performance concrete mortars with nanomaterials at elevated temperatures to simulate the behavior of binding ma- trix exposed to heat in order to increase the heat resistant behavior of the binding matrix with a focus on temperatures below 400 C. Furthermore, since there is a debate on the effects of mineral admixtures on the HPC at elevated temperatures,the findings of this study helps to identify the critical in uencing factors namely: chemical composition, moisture content, and permeability in behavior of the binding matrix at elevated temperatures. It is well established that nanomaterials can modify the above mentioned factors due to their size, shape, and solid state. Four nanomaterials, namely: nano silica with amorphous state, nano titania with both amorphous and crystal states, nano alumina with pure crystal state, and halloysite nano clay with tubular shape were chosen for this study and fractions of 1, 2 and 3% by weight of cement were added to the mixes. XRD, DSC, SEM and gas permeability tests were conducted to investigate the chemical composition and microstructural changes of the HPC mortars after being exposed to elevated temperatures up to 1000 C. The residual compressive strength, energy absorption, brittleness index and relative elastic modulus were studied to compare the mechanical properties of mortars with and without nanomaterials and to identify the most effective amount of each nanomaterials. Addition of a 1% nano silica,2% nano titania, 1% nano alumina, and 3% halloysite nano clay , as most effective amounts, enhanced the heat resistant behavior of the mortars up to 400 C in terms of residual mechanical properties and the microstructure. Up to 13% enhancement in the relative residual compressive strength, 28% enhancement in the relative elastic modulus, and 32% enhancement in the permeability of mortars were achieved when nanomaterials were added. The interlocking and filling effects of the nanomaterials played an important role in controlling the governing factor of vapor pressure in the binding matrix.